In Vitro Compatibility and Toxicity of Metarhizium anisopliae with Insecticides against Spodoptera litura - Patil, Y. B.; Bhalkare, S. K.; Nikhade, P. B.; Ingle, Y. V.; Sadawarte, A. K.; Undirwade, D. B. (International Journal of Economic Plants, 2025)
The present investigation was conducted during June, 2022 to January, 2023 at Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola (MH) to examine the compatibility of M. anisopliae with insecticides by poison food technique in completely randomized design. The data on colony diameter of M. anisopliae in each treatment was collected at 10 days after inoculation. Among the insecticides tested, Chlorantraniliprole 18.50% SC (0.006%) exhibited minimum inhibitory effect on M. anisopliae and proved most compatible insecticide tested against M. anisopliae, stood at par with M. anisopliae alone. It was followed by treatment Chlorantraniliprole 9.30%+λ-cyhalothrin 4.60% ZC (0.007%), Thiamethoxam 25% WG (0.003%), Thiamethoxam 12.60%+λ-cyhalothrin 9.50% ZC (0.009%), λ-cyhalothrin 5% EC (0.005%). However, all the insecticidal treatments proved “harmless” as per Hassan (1989) and were compatible with M. anisopliae. Besides, the experiment was performed to assess the toxicity of M. anisopliae alone and in combination with insecticides at half the recommended concentration against third instar larvae of Spodoptera litura by leaf dip bioassay. The observations on mortality of larvae of S. litura were recorded at 3, 7 and 10 days after treatment. At 10 days after treatment, Chlorantraniliprole 18.50% SC (0.003%)+M. anisopliae and Chlorantraniliprole 9.30%+λ-cyhalothrin 4.60 % ZC (0.0035%)+M. anisopliae caused promising larval mortality of cent per cent each. The combination of M. anisopliae with insecticides at half the recommended dose led to higher mortality of the S. litura.